Understanding financial risk management - Corelli, Angelo (Emerald Publishing Limited, 2019)
Financial risk management is a topic of primary importance in financial markets. It is important to learn how to measure and control risk, how to be primed for the opportunity of compensative return, and how to avoid useless exposure. This second edition of Understanding Financial Risk Management offers an updated version of its innovative approach to such issues. Angelo Corelli analyses the various types of financial risk that a financial institution now face in everyday operationsincluding market, interest rate, credit, liquidity, operational, currency, volatility, and enterprise risk. He deals with each type of risk using a rigorous mix of analytical and theoretical approaches; he gives introductory overviews to the most relevant statistical and mathematical tools; and he provides innovative analyses of all the major models available in the literature. This broad view of theory and the current state of the industry provides a friendly but serious starting point for those who encounter risk management for the first time, and it offers plenty of food for thought to more advanced readers. For its unique mix of rigour and accessibility, this book is a must-read for finance professionals, and it is of keen interest to finance students and researchers.